Inovasi Pemanfaatan Minyak Jelantah Menjadi Lilin Ramah Lingkungan di Desa Ujung Rambe Kecamatan Bangun Purba - Emma Fadhilah; Riani Sari Sembiring; Lily Novianty; Juhardi Sembiring; Khairunna Utami; Widya Fernanda Putri (Universitas Nahdlatul Ulama Sumatera Utara, 2026)
This community service program aimed to provide a solution to the problem of household used cooking oil in Ujung Rambe Village, which has the potential to cause environmental pollution and health risks if not properly managed. The program was implemented through educational activities and training on processing waste cooking oil into environmentally friendly candles with economic value. The results showed that the community was able to transform waste cooking oil into value-added products that could support the development of environmentally based businesses. Community knowledge regarding the economic value of waste cooking oil increased by 83.3%, while understanding of its impacts and management increased by 20%. Overall, this program improved community understanding of household waste management and encouraged the utilization of waste into more valuable and sustainable products.